A Stolen Name; Or, The Man Who Defied Nick Carter - Carter, Nicholas (House name) (Salt Lake City, UT : Project Gutenberg, 2020)
"A Stolen Name; Or, The Man Who Defied Nick Carter" by Nicholas Carter is a detective novel written in the early 20th century. The story revolves around the clever and audacious character of Bare-Faced Jimmy, a gentleman crook who adopts a stolen identity to claim an estate and pursue a new life of crime. As he schemes to marry the wealthy heiress Lenore Remsen, the legendary detective Nick Carter is hot on his trail, determined to uncover Jimmy$1 (Bs deception and protect those at risk. At the start of the narrative, we meet Bare-Faced Jimmy in conversation with Juno, a woman with a mysterious past. Jimmy is contemplating an audacious plan that involves assuming the identity of the deceased Ledger Dinwiddie in Virginia. While he believes this will offer him a secure life, it also sets the stage for conflict with Nick Carter, who eventually becomes aware of Jimmy's return to his former life of crime. As the plot unfolds, themes of identity, deception, and the consequences of one's past choices take center stage, hinting at an exciting and intricate cat-and-mouse game between Jimmy and Carter. (This is an automatically generated summary.)s
Release date is 2020-12-27
David Edwards, Nahum Maso i Carcases, and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Detective and mystery stories; Dime novels; Popular literature